ANALISIS PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN SUB SEKTOR LOGAM DAN SEJENISNYA (Penerapan Model Altman Z-Score yang Telah Dimodifikasi) - Yusika Yerico; Veny Anindya Puspitasari (Universitas Budi Luhur, 2019)
This study aims to analyze the potential for bankruptcy in ten metal and allied sub-sector companies listed on the Indonesia Stock Exchange (IDX) in the 2015-2018 period. The data used in this study are secondary data from annual financial statements contained in the Indonesia Stock Exchange (IDX). This study uses the Altman Z-Score model as a tool to measure the potential for bankruptcy of companies that represent financial ratios. The Altman Z-Score formula used is as follows: Z = 0.717X1 + 0.847 X2 + 3.107X3 + 0.420X4 + 0.998X5 with a zone of discrimination, if the Z value is more than 2.9 then the company is in a